Effects of preparation temperature on alkynyl-functionalized graphene oxide. Issue 11 (2nd November 2022) - Li, Yingjun; Wang, Shixia; Guo, Yakun; Zhao, Xingtao; Li, Yongsheng; Zhou, Yuanlin; Shuai, Maobing
Abstract: Alkynyl-functionalized graphene oxide (GO) is an attractive nanomaterial for many applications. Controlling the functionalization of GO is essential for the design of GO derivatives with novel properties. Here, we reported a new strategy to conveniently control the degree of alkynyl-functionalization of GO by manipulating the reaction temperature. The alkynyl-functionalized GO was characterized via Zeta potential, Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray diffraction, and Thermogravimetric analysis, confirming the covalent modification of the GO surface with propargylamine. The results showed that GO was successfully functionalized by propargylamine. And the degree of alkynyl-functionalization of GO increases with the increase in reaction temperature. The effects of the temperature on the mechanism of alkynyl-functionalized GO were also revealed. This method could be exploited to prepare functional GO with potential applications in many fields.